PENINGKATAN KOMPETENSI GURU DALAM MELAKSANAKAN EVALUASI PEMBELAJARAN OLEH KEPALA SEKOLAH DI SMAN 1 LANGGAM KABUPATEN PELALAWAN PROVINSI RIAU TAHUN PELAJARAN 2022/2023 - SRI MARTATI (LP2MTBM MAKARIOZ, 2022)
The principal is a driving tool, determining the direction of school policy, which determines how school and educational goals in general can be realized, including in improving the competence of education staff (teachers). The purpose of this study was to determine the increase in teacher competence in carrying out learning evaluations. The type of research used in this research is the school action research method (PTS). Location The research was carried out at SMAN 1 Langgam, Pelalawan Regency. Time The research was carried out in semester I July-December TP 2022/2023 2020. The subjects of the principal's action research were 19 teachers at SMAN 1 Langgam. The technique of collecting data from this school action research is through quantitative data obtained from observation and interviews. The data analysis technique used in this study is quantitative data analysis originating from the acquisition of the instrument. The results of the study show that the role of the principal is in increasing the competence of high school teachers in carrying out classroom evaluations in teaching and learning activities. From the results of the study, it showed that the teacher's competence in carrying out learning evaluation in the first cycle obtained a score of 46% in the second cycle, the teacher's ability increased to 83%. This proves that the principal's role in increasing the competence of high school teachers can improve the ability of teachers to carry out learning evaluations